2005
DOI: 10.1007/s11661-005-0332-8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of cast ingots of Al-Zn-Mg-Cu alloys modified with Sc and Zr

Abstract: The effect of combined additions of Sc and Zr on the microstructure and tensile properties of the direct chill (DC) cast ingots of developmental Al-Zn-Mg-Cu alloys has been evaluated in this work. The properties in both the longitudinal and transverse directions of the cast ingots were determined in as-cast and cast plus heat-treated conditions, at room and cryogenic temperatures.Extensive microstructural evaluation was carried out using optical and electron microscopy, including orientation image microscopy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…It is clear that all the dispersoid interspacing is greater than 100 nm, regardless of the homogenization treatment, which is in agreement with the results of other research on AA7050, [10,11] AA7475, [31] and other alloys. [14] The results of EDX analysis on dispersoids formed at different homogenization conditions are shown in Table II. It is possible to identify at least four different types of dispersoids, Zr-(type 1), Cr-(type 2), and Mn-containing (type 3) dispersoids, and those that have a combination of various elements (type 4).…”
Section: B Formation Of Dispersoidsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is clear that all the dispersoid interspacing is greater than 100 nm, regardless of the homogenization treatment, which is in agreement with the results of other research on AA7050, [10,11] AA7475, [31] and other alloys. [14] The results of EDX analysis on dispersoids formed at different homogenization conditions are shown in Table II. It is possible to identify at least four different types of dispersoids, Zr-(type 1), Cr-(type 2), and Mn-containing (type 3) dispersoids, and those that have a combination of various elements (type 4).…”
Section: B Formation Of Dispersoidsmentioning
confidence: 99%
“…[5][6][7][8][9] In the case of 7XXX-series aluminum alloys, the formation of Zr-and Sc-containing dispersoids has been investigated. [10][11][12][13][14][15][16] For example, Robson et al [10,11] investigated the effect of Zr addition on the dispersoid formation and recrystallization fraction after hot deformation. It was concluded that, when using an optimum two-step homogenization treatment, a smaller fraction of recrystallization could be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Lim et al [10] investigated the effects of constitutional changes and preheat conditions on the evolution of constitutive particles, the M, T, and S phases, and dispersoids in AA7175 and AA7050 alloys. Senkov et al [21] studied the effect of homogenization treatment on the microstructural evolution of four newly developed 7XXX series aluminum alloys to obtain optimized conditions. Jackson and Sheppard [22] studied the effect of homogenization treatment on the microstructural changes of AA7075, 7150, and 7049.…”
Section: Introductionmentioning
confidence: 99%